Shielding applications from an untrusted cloud with Haven - Baumann, Andrew; Peinado, Marcus; Hunt, Galen (11th USENIX Symposium on Operating Systems Design and Implementation (OSDI '14), 2014)
Today's cloud computing infrastructure requires substantial trust. Cloud users rely on both the provider's staff and its globally-distributed software/hardware platform not to expose any of their private data. We introduce the notion of shielded execution, which protects the confidentiality and integrity of a program and its data from the platform on which it runs (i.e., the cloud operator's OS, VM and firmware). Our prototype, Haven, is the first system to achieve shielded execution of unmodified legacy applications, including SQL Server and Apache, on a commodity OS (Windows) and commodity hardware. Haven leverages the hardware protection of Intel SGX to defend against privileged code and physical attacks such as memory probes, but also addresses the dual challenges of executing unmodified legacy binaries and protecting them from a malicious host. This work motivated recent changes in the SGX specification.